Protocol for a controlled before-after quasi-experimental study to evaluate the effectiveness of a multi-component intervention to reduce gaps in hypertension care and control in low-income communes of Medellin, Colombia - Dennis Pérez; Patrick Van der Stuyft; Alonso Soto; Esteban Augusto Londoño Agudelo; Tullia Battaglioli; José Vásquez Gómez; Hernán Aguilar Ramírez; Viviana Pérez Ospina; Armando Rodríguez Salvá; Patricia Ortiz Solórzano; Rubén Gómez-Arias (BMJ Open, 2022)
Introduction Research on public health interventions to improve hypertension care and control in low-income and middle-income countries remains scarce. This study aims to evaluate the effectiveness and assess the process and fidelity of implementation of a multi-component intervention to reduce the gaps in hypertension care and control at a population level in low-income communes of Medellin, Colombia.Methods and analysis A multi-component intervention was designed based on international guidelines, cross-sectional population survey results and consultation with the community and institutional stakeholders. Three main intervention components integrate activities related to (1) health services redesign, (2) clinical staff training and (3) patient and community engagement. The effectiveness of the intervention will be evaluated in a controlled before-after quasi-experimental study, with two deprived communes of the city selected as intervention and control arms. We will conduct a baseline and an endline survey 2 years after the start of the intervention. The primary outcomes will be the gaps in hypertension diagnosis, treatment, follow-up and control. Effectiveness will be evaluated with the difference-in-difference measures. Generalised estimation equation models will be fitted considering the clustered nature of data and adjusting for potential confounding variables. The implementation process will be studied with mixed methods. Implementation fidelity will be documented to assess to which degree the intervention components were implemented as intended.Ethics and dissemination The study protocol has been approved by the Ethics Research Committee of Metrosalud in Colombia (reference 1400/5.2), the Medical Ethics Committee of the Antwerp University Hospital (reference 18/40/424) and the Institutional Review Board of the Antwerp Institute of Tropical Medicine (reference 1294/19). We will share and discuss the study results with the community, institutional stakeholders and national health policymakers. We will publish them in national and international peer-reviewed scientific journals.Trial registration number NCT05011838.